Brand Harmony: Exploring How Destination Brand Gestalt Influences Tourist Attitudes, Satisfaction, and Loyalty - Tumober, Nadia C. G.; Langelo, Charolyn G. E.; Rantung, Danny I.; Mandagi, Deske W. (Jurnal Ekonomi, 2024)
Setting the context within Likupang, a super priority destination representing a novel facet of tourism in Indonesia, this study aims to investigate the influence of brand gestalt on tourist behavior. Specifically, the research delves into whether the brand gestalt of the destination impacts tourist attitudes, satisfaction, and loyalty. By surveying 194 visitors to Likupang, quantitative data were gathered and subsequently analyzed using Structural Equation Modeling utilizing SmartPLS 3.2. The findings reveal that brand gestalt exerts a positive and statistically significant influence on attitude, satisfaction, and tourist loyalty variables. The study sheds light on how the overall perception and presentation of the Likupang brand impact tourist attitudes, satisfaction, and loyalty. These insights provide valuable guidance for marketers and policymakers in shaping branding strategies and managing tourist experiences in Likupang, as well as potentially in other similar destinations.